2018
DOI: 10.1016/s2215-0366(18)30345-6
|View full text |Cite|
|
Sign up to set email alerts
|

The benefit of minocycline on negative symptoms of schizophrenia in patients with recent-onset psychosis (BeneMin): a randomised, double-blind, placebo-controlled trial

Abstract: SummaryBackgroundThe antibiotic minocycline has neuroprotective and anti-inflammatory properties that could prevent or reverse progressive neuropathic changes implicated in recent-onset schizophrenia. In the BeneMin study, we aimed to replicate the benefit of minocycline on negative symptoms reported in previous pilot studies, and to understand the mechanisms involved.MethodsIn this randomised, double-blind, placebo-controlled trial, we recruited people with a schizophrenia-spectrum disorder that had begun wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 38 publications
8
124
2
2
Order By: Relevance
“…Minocycline, a tetracycline antibiotic that has been shown to purportedly be neuroprotective via it's anti-inflammatory and antiapoptotic properties (106), has also been investigated in patients with schizophrenia. A recent meta-analysis demonstrated benefit for minocycline across eight randomized controlled trials (107), although the largest study to date showed no benefit for minocycline for negative symptoms, which was the primary outcome for the study (108). The heterogeneity in results across studies (both individual and meta-analyses) for NSAIDs and minocycline may suggest that there are some individuals who would benefit from anti-inflammatory medications.…”
Section: Negative Symptoms and Anti-inflammatory Treatment Trialsmentioning
confidence: 99%
“…Minocycline, a tetracycline antibiotic that has been shown to purportedly be neuroprotective via it's anti-inflammatory and antiapoptotic properties (106), has also been investigated in patients with schizophrenia. A recent meta-analysis demonstrated benefit for minocycline across eight randomized controlled trials (107), although the largest study to date showed no benefit for minocycline for negative symptoms, which was the primary outcome for the study (108). The heterogeneity in results across studies (both individual and meta-analyses) for NSAIDs and minocycline may suggest that there are some individuals who would benefit from anti-inflammatory medications.…”
Section: Negative Symptoms and Anti-inflammatory Treatment Trialsmentioning
confidence: 99%
“…The BeneMin trial3 informs clinical practice in that it should likely not be used to prevent emergence of negative symptoms in early phase patients. However, based on other trials,1 2 it is possible that minocycline is effective in patients with schizophrenia and prominent negative symptoms and/or notable inflammation.…”
Section: Do These Results Change Your Practices and Why?mentioning
confidence: 99%
“…Generalisation of the BeneMin3 trial results are limited by a selection of patients within their first psychotic episode, with mild to moderate illness severity, prominent positive symptoms and low baseline negative symptoms.…”
Section: Limitationsmentioning
confidence: 99%
“…However, a 2018 double blinded, randomised study which specifically aimed to examine the effect of this drug on negative symptoms did not find any benefit. 62 No studies of which we are aware have investigated minocycline specifically for catatonia, but reports exist of two patients with schizophrenia and prominent catatonic features who responded well to minocycline in the absence of infection. 63,64 The evidence for innate immunity…”
Section: Implications Of Treatmentmentioning
confidence: 99%